Sacral skin blood flow response to alternating pressure operating room overlay. Issue 2 (May 2019) - Karg, Patricia; Ranganathan, Vinoth K.; Churilla, Michael; Brienza, David
Abstract: Pressure injuries resulting from long surgeries may be caused by prolonged ischemia. Operating table surfaces with alternating pressure (AP) features may reduce the risk of ischemia-induced pressure injuries by providing periodic relief of blood flow occlusions. Prior research investigated alternating loading applied with a single isolated rigid indenter and demonstrated increased perfusion. This study quantified effects of an overlay with AP on sacral skin perfusion for individuals lying supine for 60-min while blood flow was monitored. The mean normalized sacral skin blood flow was found to be greater with the AP overlay over an operating table pad compared to the operating pad alone (pad with AP mean SBF = 1.45 ± 1.16, pad without AP mean SBF = 1.03 ± 0.46, p = 0.10). Peak and average interface pressure at the sacrum was significantly lower during the deflation cycle of the AP surface compared to the operating pad alone (P < 0.001), suggesting this periodic reduction resulted in higher mean blood flow. Post-hoc regression analysis showed participant body mass index was a significant predictor of the effectiveness of the AP overlay (p = 0.012). The results suggest risk for pressure injuries due to prolonged ischemia might be mitigated by the addition of an alternating pressure feature on operating table pads for lower BMI patients. Highlights: Effects on perfusion of an operating table overlay with an alternating pressure have been evaluated. Perfusion was monitored for 60 min on 20 participants with and without the alternating pressure. Sacral skin blood flow was found to be greater with the alternating pressure. Lower body mass index was a predictor of the effectiveness of the alternating pressure feature.